Blockchain Technology for Governance of Plastic Waste Management: Where Are We? - Katrien Steenmans; Phillip Taylor; Ine Steenmans (Social Sciences, 2021)
Blockchain technology is emerging as a plausible disruptor of waste management practices that influence the governance of plastics. The interest among the waste management community in the potential and fundamental changes to complex resource management associated with blockchain adoption parallels recent research in other sectors, such as finance, health, public administration, etc. During any comparable period characterized by a step-change in positive coverage of an early-stage technology, it can be challenging for actors to access a grounded, evidence-based oversight of the current state of practice and make informed decisions about whether or how to adopt blockchain technology. The current absence of such a systematic overview of recent experiences with blockchain initiatives disrupting waste practices not only limits the visibility of these experimental efforts, but also limits the learning that can be shared across waste plastics researcher and practitioner communities. This paper contributes with a current overview of blockchain technology adoption in the waste management sector, giving particular attention to implications for the governance of plastics. Our study draws on both primary interview data and secondary documentation data to map the landscape of current blockchain initiatives in the global waste sector. We identify four areas of blockchain use that are beginning to change waste management practices (payment, recycling and reuse rewards, monitoring and tracking of waste, and smart contracts). We conclude by outlining five areas of significant blockchain uses, implications, and influences of relevance to the development of circular plastic waste governance in both research and practice.